Natural play and learning spaces integrated within zoos - Bryan, Meredith (Kansas State University, 2022)
Time in nature is an essential part of childhood development to gain an understanding and relationship with nature; however, gradually, children today have reduced or limited access and opportunities to be directly engaged in natural environments. This diminishing access is exacerbated by school curricula, climate change, poor city planning, and social factors such as an increased emphasis on work and technology (Ernst 2014; Strife and Downey 2009; Szczepanski et al. 2006). This study aims to address this issue by examining how natural play and learning spaces can be integrated into informal educational institutions such as zoos. More specifically, this study investigates how the woodland natural area adjacent to Sunset Zoo in Manhattan, Kansas can serve as a natural play and learning space for local children. In addition to providing more opportunities for outdoor education, this study also shows how these natural spaces can increase the educational value of zoos. A literature review analysis, program analysis, precedent study, and a projective design were completed to explore this hypothesis. These findings offer more insights into the value of natural play and learning spaces, how they can be integrated into informal educational institutions, and how these spaces can add value to such institutions. The broader outcome of this study is related to its implications in natural play and learning spaces relationships with school curricula and childhood development.
Keywords: Natural play and learning space; Landscape architecture; Zoo design; Educational landscape; Outdoor classroom